CLASSISM DEPICTED IN IAN MCEWANS ATONEMENT - SASHIA PURNAMASANTI, EKA (LANGUAGE HORIZON, 2019)
Every living person must have motivation in life, whether its to just survive or to achieve certain dreams. Unfortunately in the process, human motivation is influenced by factors, one of which is from the economy and status. Using Ian McEwan?s novel, Atonement, as the data source, this study describes how classism is depicted in Ian McEwan?s Atonement and how the practices of classism done by the characters in the novel influence them in determining their motivations. Guided by the concept of classism by William M. Liu and the theory of needs by David C. McClelland to guide the research, the result of this study shows that the practice of classism influences the characters? psychology in determining their motivations to do actions. Keywords : class, classism, human motivation